(untitled) (Research, Society and Development, 2020)
This article aims to investigate the use of 3D technology in teaching anatomy. The main requirements of this study are to know if the use of 3D technology facilitates the learning of the contents covered in the teaching of human anatomy. It is a preliminary study that can serve as parameters for a critical, reflective and creative training of students in the health field with the use of 3D technological resources. In this review, carried out from September to October 2019, we searched for articles indexed in the electronic databases PubMed, ScienceDirect and Google Scholar, published in Portuguese and English, from 2015 to 2019. The keywords used were: “3D”, “Teaching”, “human anatomy”, “learning”. Review studies, articles with duplicate data; titles and / or abstracts that do not meet the inclusion criteria were excluded, as well as papers with a lack of relevant information, totaling 14 articles for analysis in this review. Although prospecting is the most common method of teaching anatomy, recent technologies, such as 3D software, are also considered useful teaching tools. Undergraduate students presented as the only disadvantage the need to have the technological resource to create or replicate 3D models. The vast majority of works showed student satisfaction when they used 3D models. The present work demonstrates that 3D models are viable and supplementary tools for the study of human anatomy, however there is still a need for further studies to better use these tools in the teaching-learning process of human anatomy.